Product Diversification and Implementation of Public Relations Strategy at Setu Babakan - Kusumaningrum, Anisa Putri; Waluyo, Tri; Pradini, Gagih; Saleh, Muhammad Surya; Lantana, Dhieka Avrilia (Peneliti.net, 2025)
This study discusses product diversification and the implementation of Public Relations (PR) strategies in the Betawi Setu Babakan Cultural Village, as one of the cultural tourism destinations in Jakarta. By utilizing SWOT analysis, this study explores the potential for product diversification in various zones, such as Zone A and Embryo which highlights Betawi culture through museums and traditional houses, as well as Zone B which offers typical culinary and children's play rides. The PR strategy implemented includes the use of social media for promotion, collaboration with various parties, and market research to understand visitor preferences. The results of the study show that product diversification and effective PR strategies can increase the competitiveness and sustainability of tourist destinations. However, challenges such as competition from other destinations and the impact of negative reviews on social media need to be addressed. In conclusion, by taking advantage of internal advantages and existing opportunities, Setu Babakan can strengthen its image as an attractive and sustainable cultural tourism destination.